IMPLIKASI PUTUSAN MK NOMOR 168 TAHUN 2023 TENTANG PERLINDUNGAN HAK-HAK BURUH PADA UU CIPTAKER TERKAIT PELAKSANAAN UPAH MINIMUMDI KABUPATEN KARAWANG - Muhamad Abas; Primawan Yunior Sanu; Yuniar Rahmatiar (Faculty of Law, Universitas Pekalongan, 2025)
The protection of workers' rights, particularly concerning minimum wage (UM), has become a central issue in the evolving landscape of Indonesian labor law. This study is motivated by the elimination of sectoral minimum wages through Government Regulation No. 36/2021 and the enactment of the Omnibus Law (UU Ciptaker), which sparked widespread controversy, especially regarding the protection of workers' rights and the transparency of the legislative process. Grounded in the theories of the rule of law, human rights protection, and the principles of good governance, this research employs normative legal methods using a statute approach and literature study. Data collection was conducted through the examination of primary legal materials such as laws and Constitutional Court decisions, as well as secondary legal sources including academic journals, legal books, and relevant scholarly articles. The data was analyzed qualitatively using a descriptive-analytical technique to interpret the legal implications of Constitutional Court Decision No. 168/PUU-XXI/2023. The findings reveal a misalignment between the objectives of the Omnibus Law and the implementation of workers' rights protections. Meanwhile, the Constitutional Court's decision offers a new perspective on the limitations of legislative authority, encouraging the separation of labor regulations from the Omnibus Law, and reinforcing constitutional guarantees for workers' rights. This decision has had a significant impact on wage policy, particularly in Karawang Regency, where the determination of minimum wage must now adhere to the principles of social justice, transparency, and respect for fundamental workers' rights, as subsequently implemented through the issuance of Minister of Manpower Regulation No. 16/2024 on the Determination of Minimum Wage for 2025. Overall, the Constitutional Court's decision strengthens the legal structure of Indonesian labor law, underscores the importance of the rule of law in protecting workers' rights, and marks a pivotal moment in the reform of labor regulations in line with social justice and human rights values.